2014
DOI: 10.1093/rheumatology/keu215
|View full text |Cite
|
Sign up to set email alerts
|

A study of erosive phenotypes in lupus arthritis using magnetic resonance imaging and anti-citrullinated protein antibody, anti-RA33 and RF autoantibody status

Abstract: An MRI-determined joint erosive phenotype is common in SLE, even in ACPA-negative cases. The conventional radiographic observation that anti-RA33 is not positively associated with erosion in patients with RA was also found to be the case in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…However, only a minority of the patients with SLE who have an arthritic phenotype simultaneously meet RA classification criteria [24, 25, 31]. The presence of anti-CCP antibodies is considered highly specific for RA, but can also be found in other conditions, including SLE, where frequencies from 2–17% have been described [9, 32, 4551]. Whether or not there is a true association between a positive anti-CCP test and erosive arthritis in SLE remains an open question, as several investigators have reported this [9, 4650], whereas others have not [31, 45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a minority of the patients with SLE who have an arthritic phenotype simultaneously meet RA classification criteria [24, 25, 31]. The presence of anti-CCP antibodies is considered highly specific for RA, but can also be found in other conditions, including SLE, where frequencies from 2–17% have been described [9, 32, 4551]. Whether or not there is a true association between a positive anti-CCP test and erosive arthritis in SLE remains an open question, as several investigators have reported this [9, 4650], whereas others have not [31, 45].…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have evaluated magnetic resonance imaging (MRI) in the assessment of patients with articular involvement in SLE [2932]. Recently, Ball and colleagues demonstrated that MRI is highly sensitive in identifying erosions, synovitis and bone oedema, independently of anti-CCP and RF antibody status [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of Ball et al, it has been reported that MRI was highly sensitive in identifying synovitis, bone edema, and erosive deformities, independent from anti-CCP and RF in SLE patients [32].This finding indicates that arthritis can be present even when anti-CCP and RF levels are not elevated. This finding supports the studies that were unable to show the relationship between anti-CCP and arthritis in patients with SLE.…”
Section: Discussionmentioning
confidence: 88%
“…A recent MRI study showed a high incidence of subclinical hand and wrist arthritis, with erosions not infrequently seen, which may offer an explanation for the high prevalence of arthralgias in SLE patients. [23] Arthritis in SLE should be treated with AMs, shortterm nonsteroidal antiinflammatory drugs, and lowdose (<10 mg) CS. Patients with ongoing arthritis may benefit from MTX.…”
Section: Arthritismentioning
confidence: 99%